Determinan Perilaku Pembelian Ekologis dan Konsekuensinya Terhadap Lingkungan: Perspektif Konsumen di Kota Pekanbaru Berdasarkan Kolektivisme, Perhatian Terhadap Lingkungan, Efektivitas Konsumen dan Kesediaan Membayar - Julina Julina (Kutubkhanah, 2013)
The purpose of this study is to examine the determinants of ecologically purchase behavior. Understanding of these factors is important to know the buying behavior of people who can contribute to the environmental rescue. Based on the scale developed from a variety of previous research, this study examines the effect of collectivism, environmental concern, perceived onsumer, and willingness to pay more towards ecological buying behavior in Pekanbaru. Data was collected using questionnaires, then analyzed using Structural Equation Modeling. The research proves that collectivism affect environmental concerns and perceived consumer effectiveness. Furthermore, environmental concerns affect the willingness to pay higher prices. behavior. However, in this study the effect of collectivism and willingness to pay more toward ecologically communications program precisely and in accordance with customer expectations, while for the government, the results of this study can be used as input to determine the policies that can save the environment.